Langgam Makassar: the adaptation of keroncong to local music in Makassar - Hudzaifah, Adiatma; Mistortoify, Zulkarnain (Pascasarjana Institut Seni Indonesia Surakarta, 2023)
The musical landscape of Makassar features a unique variant of keroncong known as